Pengaruh Kepemimpinan Melayani Kepala Sekolah dan Budaya Kerja Terhadap Produktivitas SMA di Sumbawa Barat - Ahmad Zulfikar; Akhairuddin Akhairuddin (Universitas Pendidikan Indonesia, 2022)
The purpose of this study is to examine how much influence the school principal's servant leadership and work culture have on the productivity of high school in West Sumbawa. The method used in this study was a survey method with a quantitative approach, the population in this study was school principals and teachers in 16 units of SMA/MA in West Sumbawa. 100 samples were selected using a simple random sampling technique employing the formula from Taro Yamane, while questionnaires were used for the data collection instrument. Furthermore, the data analysis require-ments were carried out on the instrument with a construct validity test through expert judgment and factor analysis and reliability test with Alpha Cronbach technique and then the data analysis was conducted by using descriptive statistical methods and multiple regression utilizing SPSS. 21.0. The results of this study indicate that there is a significant influence between the school principal’s servant leadership and work culture on school productivity. Currently, many schools experience a decrease in productivity therefore the quality of the high school graduates is not optimal. Among the factors that contribute to school productivity are servant leadership and work culture.